1998
DOI: 10.1097/00000542-199802000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Storage and Emptying Functions of the Urinary Bladder after Spinal Anesthesia with Lidocaine and with Bupivacaine in Men 

Abstract: Spinal anesthesia with lidocaine and with bupivacaine causes a clinically significant disturbance of bladder function due to interruption of the micturition reflex. The urge to void disappears quickly and bladder function remains impaired until the block has regressed to the third sacral segment in all patients. With long-acting local anesthetics, the volume of accumulated urine may exceed the cystometric bladder capacity. With respect to recovery of urinary bladder function, the use of short-acting local anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
2
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(105 citation statements)
references
References 15 publications
2
95
2
6
Order By: Relevance
“…Spinal anesthesia causes vesical function disorders due to interrupted micturition reflex. Vesical dysfunction remains until blockade is reduced to the third sacral segment in all patients 18 . With long-action anesthetic, the accumulated amount may exceed the cystometric capacity of the bladder 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Spinal anesthesia causes vesical function disorders due to interrupted micturition reflex. Vesical dysfunction remains until blockade is reduced to the third sacral segment in all patients 18 . With long-action anesthetic, the accumulated amount may exceed the cystometric capacity of the bladder 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal bupivacaine 10 mg was associated with prolonged return of detrussor function (462 ± 61 min) compared to intrathecal lidocaine 100 mg (235 ± 30 min). 37 The urine volume generated in the bupivacaine group in this study was 1.6 times the "cyctometric capacity" (the bladder volume required to develop an urge to void preoperatively). Short-acting spinal anesthetics for low risk Old age 3.…”
Section: Mandatory Voiding Prior To Dischargementioning
confidence: 63%
“…33,34 Identified risk factors for postoperative urinary retention are presented in Table IV. [35][36][37][38] In current practice, voiding is not a requirement before discharge from the ASU, as it could delay the discharge of 5%-11% of patients who have no risk factors for urinary retention after ambulatory surgery. 39 The incidence of urinary retention, as defined by the inability to void at a bladder volume of 600 mL, is less than 1% in low risk ambulatory surgical patients.…”
Section: Mandatory Voiding Prior To Dischargementioning
confidence: 99%
“…Axelesson et al found that urinary retention has a close relationship with sensory block (28). Kamphius et al found that reversal of urinary retention was related with regression of the block to the third sacral segment and found that the incidence of urinary retention was lower with unilateral and lowdose spinal anesthesia (29).…”
Section: Discussionmentioning
confidence: 99%